2018
DOI: 10.3389/fimmu.2018.01200
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies to Cytosolic 5′-Nucleotidase 1A in Primary Sjögren’s Syndrome and Systemic Lupus Erythematosus

Abstract: IntroductionAutoantibodies to cytosolic 5′-nucleotidase 1A (cN-1A; NT5C1A) have a high specificity when differentiating sporadic inclusion body myositis from polymyositis and dermatomyositis. In primary Sjögren’s syndrome (pSS) and systemic lupus erythematosus (SLE) anti-cN-1A autoantibodies can be detected as well. However, various frequencies of anti-cN-1A reactivity have been reported in SLE and pSS, which may at least in part be explained by the different assays used. Here, we determined the occurrence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 18 publications
0
33
0
Order By: Relevance
“…The clinical utility of anti-NT5c1A from a diagnostic, prognostic and treatment perspective in sIBM as previously reported is summarized in Table 1 and odds ratios (OR) with 95% confidence intervals (CIs) of six eligible studies (see section Methods and Supplemental Table 1) are displayed as a logarithmic forest plot in Figure 1. A wide range of sensitivities of anti-NT5c1A antibodies is reported in sIBM ranging from 33 to 80% and it has been suggested that anti-NT5c1A may not be as reliable a biomarker for sIBM as previously thought (812, 14). It is also unclear as to whether anti-NT5c1A antibodies are associated with a particular sIBM phenotype, such as increased disease severity, progression, mortality, or response to treatment (2, 810).…”
Section: Introductionmentioning
confidence: 98%
“…The clinical utility of anti-NT5c1A from a diagnostic, prognostic and treatment perspective in sIBM as previously reported is summarized in Table 1 and odds ratios (OR) with 95% confidence intervals (CIs) of six eligible studies (see section Methods and Supplemental Table 1) are displayed as a logarithmic forest plot in Figure 1. A wide range of sensitivities of anti-NT5c1A antibodies is reported in sIBM ranging from 33 to 80% and it has been suggested that anti-NT5c1A may not be as reliable a biomarker for sIBM as previously thought (812, 14). It is also unclear as to whether anti-NT5c1A antibodies are associated with a particular sIBM phenotype, such as increased disease severity, progression, mortality, or response to treatment (2, 810).…”
Section: Introductionmentioning
confidence: 98%
“…Anti‐cN1A antibodies directed to a 43‐kd muscle‐specific autoantigen are a useful biomarker for sIBM, have high specificity in distinguishing sIBM from other subsets of inflammatory myopathies, and may have a role in pathogenesis. Importantly, however, they are not disease‐specific and have also been detected in patients with pSS …”
Section: Discussionmentioning
confidence: 99%
“…One study described 8 of 36 (22%) of patients with pSS and myalgia, who underwent muscle biopsy, showed histopathological features of IBM, although none had clinical features characteristic of this condition . The detection of anti‐cN1A, which is selectively associated with IBM rather than other forms of idiopathic inflammatory myopathies (IIM) in a substantial proportion (12%) of patients with pSS, suggests a specific predilection for sIBM among patients with pSS.…”
Section: Discussionmentioning
confidence: 99%
“…Antibodies against cN1A were described in IBM, PM/DM, Ssc, SLE, and Sjögren's syndrome (range 0-37%). However, associations with ILD have not been identified [26,27,[30][31][32]43,45]. We demonstrated novel data regarding the presence of cN1A antibodies in ILDs, including ASS, HP, and IPF.…”
Section: Discussionmentioning
confidence: 86%
“…Here, we focus on relatively unknown antibodies, including antibodies specific for asparaginyl-t-RNA synthetase (anti-Ks), tyrosyl-t-RNA synthetase (anti-Ha), phenylanyl-t-RNA synthetase alpha (anti-Zoα), and cytosolic-5-nucleotidase-1A (anti-cN1A). Circulating antibodies specific for Ks, Ha, and cN1A have been described in inclusion body myositis (IBM), systemic sclerosis (Ssc), and Sjögren's syndrome, whereas anti-Zo has been identified in anti-synthetase syndrome (ASS) with ILD [26][27][28][29][30][31][32][33][34][35][36]. However, data are scarce on the prevalence and associations of these autoantibodies in CTD-ILD and other ILD.…”
Section: Introductionmentioning
confidence: 99%